Calpain mediates caspase-dependent apoptosis initiated by hydrogen peroxide in pancreatic acinar AR42J cells*. (May 2013) - Weber, H.; Müller, L.; Jonas, L.; Schult, C.; Sparmann, G.; Schuff-Werner, P.
Abstract Several studies have shown that oxidative stress induces apoptosis in many cellular systems including pancreatic acinar cells. However, the exact molecular mechanisms leading to apoptosis remain partially understood. This study aimed to investigate the role of the cytosolic cysteine protease calpain in H2O2-induced apoptosis in pancreatic AR42J cells. Apoptosis was evaluated using flow cytometric analysis of sub-G1 DNA populations, electron-microscopic analysis, caspase-3-specific αII-spectrin breakdown, and measuring the proteolytic activities of the initiator caspase-12 and caspase-8, and the executioner caspase-3. H2O2 induced an increase in the calpain proteolytic activity immediately after starting the experiments that tended to return to a nearly normal level after 8 h and could be attributed to m-calpain. Whereas no caspase-12, caspase-8 and caspase-3 activations could be detected within the first 0.5 h, significantly increased proteolytic activities were observed after 8 h compared with the control. At the same time, the cells showed first ultrastructural hallmarks of apoptosis and a decreased viability. In addition, αII-spectrin fragmentation was identified using immunoblotting that could be attributed to both calpain and caspase-3. Calpain inhibition reduced the activities of caspase-12, caspase-8, and caspase-3 leading to a decrease in the number of apoptotic cells. Immunoblotting analyses of caspase-12 and caspase-8 indicate that calpain may be involved in the activation process of both proteases. The results suggest that H2O2-induced apoptosis of AR42J cells requires activation of m-calpain initiating the endoplasmic reticulum stress-induced caspase-12 pathway and a caspase-8-dependent pathway. The findings also suggest that calpain may be involved in the execution phase of apoptosis.